PENGARUH PEMBERIAN RANSUM DENGAN DOSIS HERBAL YANG BERBEDA TERHADAP LEMAK DARAH AYAM PERSILANGAN - Abraham Hendry, Rudy Sutrisna, Syahrio Tantalo, dan Farida Fathul (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
This study aimed to determine the effect of giving rations with different of herbs dosages on the blood lipid of crossbred chicken and to find out the best dosage of herbs in ration that affect the blood lipid of crossbred chicken. This research was conducted in 19 September 2018 to 26 September 2018 in the poultry house of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The examination of blood lipid levels was conducted at Lampung UPTD Laboratory Hall. The chickens used were crossbred chickens between male Lohman brown and female kampong (3/4 Lohman brown +1/4 kampong) layer phase (48 weeks) with total of 12 chickens. The experimental design used was completely randomized design (CRD) with 4 treatments and 3 replications. The treatment given were H0: without herbs, H1: 1g/kg herbs, H2 : 2g/kg herbs, and H3: 3g/kg herbs. The data obtained were analyzed using analysis of variance with significant level of 5%. The variables observed were consumption of rations, cholesterol, high density lipoprotein, and triglyceride content. The results showed that the rations with different herbs had no significant effect (P> 0.05) on the blood lipid levels of the crossbred chicken. Keywords: Rations, Herbs, Blood lipids, Crossbred chicken